Pengaruh Tingkat Intensitas Komunikasi Orangtua terhadap Prestasi Belajar Siswa: Studi Deskriptif Analitis Mengenai Pengaruh Tingkat Intensitas Komunikasi Orangtua terhadap Prestasi Belajar Siswa Kelas VIII MTs Al-Bazari Parungkuda Kabupaten Sukabumi - Itsna Nurhayat Effendie; Hamdi Yusup; Aris Gundara (Jurnalika : Jurnal Ilmu Komunikasi, 2022)
The implementation of education is a shared responsibility, the government, the community, and parents. However, the implementation has not yet been agreed upon by the interested parties. Parents fully trust the school with the hope that their child will get a good education. Schools and families contribute to the achievement of the quality of education, and the quality of learning depends on the condition of the students' families. Learning achievement is the result of an educational system so that the level of success is determined and influenced by elements of the system, such as input input, input input, and environmental input. The factors that influence learning achievement are external and internal factors. However, the focus of the study in this research is external factors in the form of social and non-social factors. Social factors include the family environment including how to educate, home atmosphere, community, playmates, teachers and staff at school. This study aims to determine the effect of the intensity level of parent-student communication on the level of student achievement at MTs Al-Bazari Parungkuda Sukabumi. Sampling was carried out in a systematic random sampling so that a sample of 60 people was obtained from a population of 242 people. Collecting data by observation, questionnaires, and documentation. The data obtained were analyzed by descriptive statistics, quantitative and inferential statistical analysis. The results showed that the intensity level of parent-student communication had a positive and significant effect on the level of student achievement with the results of the regression equation obtained were = 5.429 + 0.0334x and the value of Fh = 5.410 which had a value of 0.024 which was smaller than = 0 ,05. This means that the regression model obtained is significant and can be used to estimate the value of y if x is known, and the value of the determinant R2 = 0.085 which means that there is an 8.5% variation in the level of student learning achievement influenced by the intensity level of parent-student communication.